“Estudio de factibilidad para la creación de una empresa productora y comercializadora de Té de Pitahaya ubicada al norte de la ciudad de Quito” - Guachamin Mantilla, Meliza Monserrat (2013)
The lack of creativity to exploit our country's fruit motivates us to seek new opportunities to promote a growing culture, so this project is based in a study for the creation of a business of producing and commercializing "pitahaya tea" that will be located on north of Quito city. Pitahaya (A.K.A. The dragon fruit) has great medicinal and nutritional benefits but they are unknown since in the market study it was determined that only 40% of the population has consumed this fruit. That is why this project will promote its consumption through our products such as tea and pulp